Aesthetics of Theory in the Modernist Era - Bakoeva Saodat Shuhratovna (Indonesian Journal of Innovation Studies, 2022)
the article provides an overview of the aesthetics of modernist literature. However, there are also many ideas about the aesthetics and psychologicalprocess of modernist literature. There are also analyses through examples of the aesthetics of theory in the modernistic period.